Exploring the Impact of Digital Divide on Quality of Work Life of Employees: Empirical Evidence from Nepal - Bhattarai, Mandip; Rai, Arjun (Journal of Janta Multiple Campus, 2025)
This study examined the effect of access to technology, learning challenges, and age on quality of work life. This study used a survey questionnaire to collect primary data from 111 respondents. In this study, the researchers used a cross-sectional research design. Descriptive and inferential statistical tools were used in this study. The ordinary least squares multiple regression model was used to examine the impact of independent variables on dependent variables. The reliability test revealed a robust internal consistency. The regression analysis revealed a significant positive impact of access to technology and learning challenges on the quality of work-life. However, the variable age had an insignificant negative impact on the quality of work life. The results suggested that access to technology and challenges significantly influence employees' quality of work life. Subsequent studies can be conducted by including additional variables affecting the quality of work life, using longitudinal studies to monitor temporal changes, and analyzing the impact of various demographic variables, including educational background, on job-related outcomes.